2014
DOI: 10.1620/tjem.233.197
|View full text |Cite
|
Sign up to set email alerts
|

Urinary 8-Hydroxydeoxyguanosine Is a Potential Indicator for Estimating Pulmonary Rehabilitation-Induced Oxidative Stress in COPD Patients

Abstract: Chronic obstructive pulmonary disease (COPD) is the most common chronic lung disease and is an important cause of morbidity worldwide. The aim of this study was to evaluate whether pulmonary rehabilitation (PR) improves the oxidant/antioxidant imbalance, exercise capacity and health-related quality of life (HRQL) in patients with different stages of COPD. Eighteen stable COPD patients participated in 8-week PR; the exercise intensity was set at 70% of the V 4 O 2 peak. Subjects were divided into 2 groups: mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…A total of 4479 studies were initially identified, 3242 full-text articles screened, 43 peer-reviewed studies included in the Systematic Review [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ] and 11 articles included in the meta-analysis on DNA oxidation products [ 27 , 28 , 36 , 37 , 52 , 53 , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 4479 studies were initially identified, 3242 full-text articles screened, 43 peer-reviewed studies included in the Systematic Review [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ] and 11 articles included in the meta-analysis on DNA oxidation products [ 27 , 28 , 36 , 37 , 52 , 53 , …”
Section: Resultsmentioning
confidence: 99%
“…Refs. [ 27 , 28 , 32 , 35 , 36 , 39 , 41 , 42 , 43 , 44 , 46 , 47 , 48 , 49 , 51 , 53 , 54 , 55 , 57 , 59 , 60 , 61 , 63 , 66 , 67 ] reported significant oxidative stress changes due to physical activity. Oxidative stress biomarkers were generally increased after vigorous physical activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to date, investigators have found that COPD patients exhibit only a minor increase or even a decrease in muscle antioxidant potential following exercise training 79,80) , although there is a lack of data about the relationship between exercise training and muscular antioxidant capacity in COPD patients. Even though endurance exercise training is performed as part of pulmonary rehabilitation, it could cause oxidative stress in patients with severe COPD 81,82) . For example, Barreiro et al 81) found increased nitrotyrosine (a marker for nitrosative stress) in quadriceps muscle of COPD patients after a 3-week endurance exercise program.…”
Section: Acute Exercise and Exercise Training In Copdmentioning
confidence: 99%
“…For example, Barreiro et al 81) found increased nitrotyrosine (a marker for nitrosative stress) in quadriceps muscle of COPD patients after a 3-week endurance exercise program. Nemoto et al 82) reported an increase in urinary 8-hydroxydeoxyguanosine (a marker for oxidized DNA) in COPD patients with very severe airflow obstruction, but not in moderate-to-severe COPD patients following an 8-week pulmonary rehabilitation program. It should be noted that even standard exercise programs could cause oxidative stress in COPD patients, particularly muscle-wasted or severely affected COPD patients.…”
Section: Acute Exercise and Exercise Training In Copdmentioning
confidence: 99%